Optimal Exchange Rate Policy: The Case of Iceland - Maŕ Gu∂mundsson; Thoŕarinn G. Pet́ursson; Arnoŕ Sighvatsson (Norges Bank, 2001)
Presented at the workshop ''The conduct of monetary policy in open economies'' on 26-27 October 2000;This paper analysis the appropriate exchange rate arrangement for Iceland, given its structural characteristics, on the one hand, and the need for a credible nominal anchor for monetary policy, on the other. It also discusses the current regime of a currency peg, its rationale, its success in terms of achieving its goals, and how the apparent conflict between the exchange rate arrangement suggested by the structural characteristics of the economy and the arrangement actually chosen, has been resolved. Finally, the paper provides an assessment of alternative future exchange rate regimes. The paper argues that at this point of time a formal inflation target with a flexible exchange rate is the best available option. This does not, however, preclude membership in a monetary union at a later date.
hdl:11250/2498709
Keywords: E52; 330; Iceland; exchange rate regime; optimal currency area